3'-Azido-3'-deoxythymidine resistance suppressed by a mutation conferring human immunodeficiency virus type 1 resistance to nonnucleoside reverse transcriptase inhibitors. - Larder, B A (1992)
Nonnucleoside reverse transcriptase (NNRT) inhibitors (R82913; (+)-S-4,5,6,7-tetrahydro-9-chloro-5-methyl-6-(3-methyl-2-butenyl)- imidazo[4,5,1-jk][1,4]-benzodiazepin-2(1H)-thione; Cl-TIBO; and BI-RG-587, nevirapine) were used to select resistant human immunodeficiency virus type 1 (HIV-1) variants by passage in cell cultures of wild-type or 3'-azido-3'-deoxythymidine (zidovudine; AZT)-resistant strains. Similar to other NNRT inhibitors, Cl-TIBO induced a single mutation (Y181 to C) in reverse transcriptase (RT) that accounted for the resistance. BI-RG-587 induced a different mutation (V106-->A) in AZT resistance backgrounds. A series of viable HIV-1 variants was constructed by site-directed mutagenesis of the RT, which harbored multiple drug resistance mutations, including Y181 to C. HIV-1 that was co-resistant to NNRT inhibitors and 2',3'-dideoxyinosine resulted when a 2',3'-dideoxyinosine resistance mutation (L74 to V) was also present in RT. By contrast, however, the Y181 to C mutation in an AZT resistance background significantly suppressed resistance to AZT, while it conferred resistance to NNRT inhibitors. However, the V106-->A substitution did not cause suppression of preexisting AZT resistance. Since certain combinations of nucleoside analogs and NNRT inhibitors might result in the development of co-resistance, careful analysis of clinical isolates obtained during combination therapy will be needed to determine the potential significance of these observations.